DAMPAK IMPLEMENTASI KURIKULUM 2013 TERHADAP JAM PELAJARAN BAHASA JEPANG PADA TINGKAT SMA/MA DI WILAYAH JAWA TIMUR - Ulfah Sutiyarti (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
This research aims to determine the impact of the implementation of the curriculum in 2013 against Japanese subjects senior high school level in East Java. This study used mixed methods (quantitative and qualitative), respondents who used 67 teachers Japanese senior high school in East Java, the data retrieval techniques such as questionnaire. From this research it is known that 47 respondents (70%) of the total respondents experienced a decrease in the number of teaching hours. It found that the Japanese teacher hours reduce from 25 hours/week to 18 hours/week. If calculated by the percentage of respondents, 70% of respondents had reduction in their teaching hours, 11% of respondents lost teaching hours, 6% is still the same amount of teaching and only 8% are increasing the number of hours of teaching. Based on the analysis of different test average number of hours of teaching Japanese teacher in East Java obtained that Ho Rejected and H1 accepted, meaning that there is a real difference between the hours of teaching Japanese before and after the imposition of Curriculum 2013.